PEMBERDAYAAN MASYARAKATMELALUI KOMUNIKASI DAKWAH DAN LITERASI KEAGAMAAN DI DESA SEI AWAN KIRI KABUPATEN KETAPANG - Lutfiyatun Nakiyah; Solihin, Syarif Romi, Yogi Aliarda, Syahril, Pahjar Riyudha (Adiba Aisha Amira, 2024)
This Community Service Program (PKM) was carried out by lecturers and students of the Islamic Communication and Broadcasting (KPI) Department at STAI Al-Haudl Ketapang with the aim of enhancing the religious capacity and literacy of the community in Sei Awan Kiri Village, Ketapang Regency. The phenomenon of low religious literacy, particularly among the younger generation, as well as the lack of systematic educational spaces, became the foundation for this program. The implementation method employed a participatory approach, including observation, counseling, Qur’an reading training, religious studies, group discussions, and mentoring. The results of the program showed an improvement in the community’s understanding of practical worship, an increase in Qur’an reading skills among children and youth, and the growth of a spirit of togetherness in strengthening Islamic literacy. This program also had an impact on lecturers and students by strengthening their practical da’wah competencies and providing experience in community empowerment. Thus, this PKM serves as a collaborative medium between higher education institutions and the community in fostering religious awareness and shaping Islamic literacy traditions in rural areas.